Pengaruh Kualitas Kehidupan Kerja Dan Konflik Peran Terhadap Komitmen Organisasi Dengan Kepuasan Kerja Sebagai Variabel Intervening Di Bps Propinsi D.I. Yogyakarta - Sudaryatun, Wiji (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2014)
This study aimed to examine the effect of the quality of working life and role conflict on organizational commitment with job satisfaction as an intervening variable in BPS Province D.I Yogyakarta. The study was conducted in BPS Province D.I. Yogyakarta, where all employees are sampled, so this research is called the study population.Collecting data using a survey questionnaire method. The number of respondents as many as 77 people, since the year 2012, there are 2 employees who are learning task, one person retired and one person died. The number of questionnaires were distributed according to the number of respondents ie 77Â  sets, and return as many as 77. The study was conducted in mid-December.From this research result that (a). quality of work life significant positive effect on job satisfaction, (b). Role conflict was not a significant negative effect on job satisfaction, (c). Quality of work life significant positive effect on organizational commitment, (d). Conflict is not the role of significant negative effect of organizational commitment, (e). Job satisfaction significant positiveÂ  effect on organizational commitment, (f). Job satisfaction mediates the indirect effect of quality of work life for organizational commitment, and (g). Job satisfaction mediates the indirect effect of the quality of the conflicting roles of organizational commitment.